Towards Sustainable Water Resource Management in Rural Nigeria: The Role of Communities - Arimoro, Augustine Edobor; Musa, Habibah (Journal of Sustainable Development Law and Policy, 2025)
Access to water is crucial for healthy living and survival. In developing countries such as Nigeria, rural communities often suffer from a severe shortage of the supply of fresh, potable water. The need to change the tide has led to the inclusion of the adequate availability of water for all as one of the 2030 United Nations Sustainable Development Goals. Evidence shows that the lack or poor supply of freshwater could lead to a prevalence of waterborne diseases and might negatively affect economically important activities. While water sustainability deals with ensuring adequate supply of water for the present and future generations, water resource management is the strategy for achieving water sustainability. Considering the above, this article examines the literature on water resource management vis-à-vis the legal framework for water management in Nigeria. The article notes that rural communities in the country have a critical role to play in water resource management in the country and in the quest to attain the goals for water. It is recommended that policies should be implemented to provide for sustainable management of water as well as a strategy for educating rural communities on what they must do to achieve the Sustainable Development Goals for water management in Nigeria at the rural community level. For example, there is a need to provide for private sector led water development projects in rural areas backed by government subsidy as well as programmes to enlighten community leaders on their role in ensuring water sustainability.